Effect of transcranial static magnetic stimulation over unilateral or bilateral motor association cortex on performance of simple and choice reaction time tasks - Matsumoto, Takuya; Watanabe, Tatsunori; Ito, Kanami; Horinouchi, Takayuki; Shibata, Sumiya; Kurumadani, Hiroshi; Sunagawa, Toru; Mima, Tatsuya; Kirimoto, Hikari (Frontiers in Human Neuroscience, 2023)
Background: Transcranial static magnetic stimulation (tSMS) is a non-invasive brain stimulation technique that place a strong neodymium magnet on scalp to reduce cortical excitability. We have recently developed a new tSMS device with three magnets placed close to each other (triple tSMS) and confirmed that this new device can produce a stronger and broader static magnetic field than the conventional single tSMS. The aim of the present study was to investigate the effect of the conventional single tSMS as well as triple tSMS over the unilateral or bilateral motor association cortex (MAC) on simple and choice reaction time (SRT and CRT) task performance. Methods: There were two experiments: one involved the conventional tSMS, and the other involved the triple tSMS. In both experiments, right-handed healthy participants received each of the following stimulations for 20 min on different days: tSMS over the unilateral (left) MAC, tSMS over the bilateral MAC, and sham stimulation. The center of the stimulation device was set at the premotor cortex. The participants performed SRT and CRT tasks before, immediately after, and 15 min after the stimulation (Pre, Post 0, and Post 15). We evaluated RT, standard deviation (SD) of RT, and accuracy (error rate). Simulation was also performed to determine the spatial distribution of magnetic field induced by tSMS over the bilateral MAC. Results: The spatial distribution of induced magnetic field was centered around the PMd for both tSMS systems, and the magnetic field reached multiple regions of the MAC as well as the sensorimotor cortices for triple tSMS. SD of CRT was significantly larger at Post 0 as compared to Pre when triple tSMS was applied to the bilateral MAC. No significant findings were noted for the other conditions or variables. Discussion: We found that single tSMS over the unilateral or bilateral MAC did not affect performance of RT tasks, whereas triple tSMS over the bilateral MAC but not over the unilateral MAC increased variability of CRT. Our finding suggests that RT task performance can be modulated using triple tSMS.